1998
DOI: 10.4269/ajtmh.1998.59.302
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DP control of human Schistosoma haematobium infection.

Abstract: Abstract. The DPA1 and DPB1 alleles of the major histocompatibility complex (MHC) class II were determined in 110 patients and 120 healthy controls of a Gabonese population from an area endemic for Schistosoma haematobium infection. The MHC-DP alleles of the variable second exons and their human leukocyte antigen (HLA) epitopes were correlated with egg excretion, interleukin-4 and interferon-␥ patterns, and bladder abnormalities, as detected by ultrasonography. A methionine at position 11 of the DP␣ molecule (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…In support of this hypothesis, several previous studies have demonstrated associations of HLA class II alleles with the susceptibility or course of infectious disease. These have included the association of the class II HLA-DRB1*1302/DQB1*0501 haplotype with mild Plasmodium falciparum malaria in The Gambia [14], class II DR*04 alleles with more-severe malaria in Gabon [15], and a controversial proposed role for a specific variable region, as opposed to an allele (position 11 of the class II DP alpha chain), in the outcome of Onchocerca volvulus and Schistosoma haematobium infections [15,16]. The HLA-DRB1*1302 allele is associated with the clearance of hepatitis B virus in The Gambia [17], and, conversely, class II DQA1*0501 and DQB1*0301 alleles are associated with persistent hepatitis B virus infection in African Americans [18].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, several previous studies have demonstrated associations of HLA class II alleles with the susceptibility or course of infectious disease. These have included the association of the class II HLA-DRB1*1302/DQB1*0501 haplotype with mild Plasmodium falciparum malaria in The Gambia [14], class II DR*04 alleles with more-severe malaria in Gabon [15], and a controversial proposed role for a specific variable region, as opposed to an allele (position 11 of the class II DP alpha chain), in the outcome of Onchocerca volvulus and Schistosoma haematobium infections [15,16]. The HLA-DRB1*1302 allele is associated with the clearance of hepatitis B virus in The Gambia [17], and, conversely, class II DQA1*0501 and DQB1*0301 alleles are associated with persistent hepatitis B virus infection in African Americans [18].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, disease severity in infection with the three pathogenic schistosome species (S. mansoni, Schistosoma japonicum, and Schistosoma hematobium) has been linked with a variety of HLA haplotypes (14,15,17,21). On the other, a region outside the MHC on chromosome 5q31-q33, containing the SM1 gene, has been found to control disease susceptibility vs resistance in terms of intensity of infection (16,39,50); this region includes a cluster of cytokine/cytokine receptor genes that influence the outcome of immune responses against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported associations between DP alleles and human leukaemia (Pawelec et al, 1988;Taylor et al, 1995Taylor et al, , 2002. Furthermore, DP alleles are known to be associated with, or to act as restriction elements for a number of parasitic (Meyer et al, 1994;May et al, 1998), microbial and viral diseases, including hepatitis B and rabies (Celis and Karr, 1989;Celis et al, 1990), herpes simplex (Koelle et al, 2000), streptococcus (Dong et al, 1995), dengue virus (Kurane et al, 1993;Okamoto et al, 1998), Epstein -Barr virus (Voo et al, 2002), respiratory syncytial virus (RSV) (De Graaf et al, 2004;De Waal et al, 2004), and HIV (Cohen et al, 2006).…”
mentioning
confidence: 99%